A criminalização do porte de cannabis sustentada pelo racismo: um estudo sobre a criminalização e análise de 491 processos de porte de maconha no estado de São Paulo - Castro, Mariana Gomes de (2021)
This study aims to analyze the criminalization of recreational use of marijuana in Brazil. It approaches the historical prism in Brazil under the aspect of the prohibition resulting from racism and also the prohibitionist policy imposed by the United States of America. In relation to Brazil, the study indicates the effects of criminalization on the black population and prison inflation, as well as the current drug legislation, in addition to the extraordinary appeal 635659 that is being processed in the Supreme Court. The judicial process faced by the user of marijuana was analyzed in an analysis of 491 cases under the scrutiny of the Court of Justice of the State of São Paulo with the exposure of the penalties applied, duration of the process since the opening of the Circumstantial Term, counties higher rates of conviction, level of study and quantity apprehended and the possible effects of decriminalization in terms of the efficiency of justice.